Effective degradation of the antineoplastic doxorubicin by electrochemical oxidation on boron doped diamond - Ferreira Garcia, Luane; Gonçalves Moreno, Emily Kussmaul; Barroso Brito, Lara; Rodrigues de Oliveira, Gisele Augusto [UNESP]; Linares, José J.; de Souza Gil, Eric (Elsevier, 2020)
Doxorubicin (DOX) is an antineoplastic drug widely used to treat many types of cancer. Its presence in hospital effluents turns mandatory the application of efficient processes in the treatment of this pollutant, due to the toxicological damages that DOX causes to the environment. This study presents the results of the electrolysis of DOX, for the first time, on non-active boron doped diamond (BDD) anodes. Electrolysis with Na2SO4 and NaCl were performed. Rapid and more efficient removal was achieved in NaCl-based electrolysis with lower energy consumption, due to a more intense generation of oxidants, among which active chlorine stands out. After treatment, the resulting solutions were tested using fish embryo acute toxicity test and comet assay with zebrafish (Danio rerio). NaCl-based DOX electrolysis allows the complete removal of the DOX toxicity and mutagenicity, whereas Na2SO4-based electrolysis was not completely efficient. Finally, a tentative degradation mechanism for the electrochemical treatment of DOX has been proposed based on mass spectra obtained from the degraded samples.
Keywords: Antineoplastic; Boron doped diamond; Degradation mechanism; Electro-oxidation; Toxicity